Studi Mobile Commerce Di Bandar Lampung - Tristiyanto Tristiyanto; Syintia Dwi Nurrahmi; Yunda Heningtyas (Universitas Lampung, 2021)
The online shopping process in Bandar Lampung is facilitating by mobile commerce online shopping. The factor of using online shopping mobile commerce has never been analyzed based on the public perception in Bandar Lampung. This research discusses using mobile-commerce online shopping using the UTAUT2 model with Perceived Risk manifestations, namely Security Risk and Privacy Risk. The mobile commerce applications analyzed were Shopee, Lazada, Tokopedia, Bukalapak, and Blibli. The purpose of this research was to determine the UTAUT2 variable with the manifestation of Perceived Risk, namely Security Risk and Privacy Risk, which affect the use of online shopping mobile commerce. The data analysis method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The total number of respondents obtained was 183 respondents. The data tested were 373 data. This research results from the factors that most influence the behavioral intention and use behavior of mobile commerce online shopping is a habit.